Type and Frequency in Use of Nutraceutical and Micronutrient Supplementation for the Management of Polycystic Ovary Syndrome: A Systematic Scoping Review - Nicole Scannell; Evangeline Mantzioris; Vibhuti Rao; Chhiti Pandey; Carolyn Ee; Aya Mousa; Lisa Moran; Anthony Villani (Biomedicines, 2023)
Lifestyle strategies are considered first-line treatment for the management of polycystic ovary syndrome (PCOS). However, complementary therapies, including nutrient supplementation, have been identified as a potential adjunct therapy. Therefore, we systematically mapped the available literature to identify the type and frequency of the use of nutraceutical and micronutrient supplementation for the management of PCOS features. A systematic search of the literature was conducted using CINAHL, Cochrane reviews, Medline, PsycINFO, Scopus and LILACS. All types of study designs were included if they reported on the use of nutraceuticals and/or micronutrient supplementation on features of PCOS in women aged ≥18 years. A total of 344 articles were included. Forty-one supplements were identified, with the most frequently investigated being inositols (n = 86), vitamin D (n = 53), N-acetylcysteine (n = 27) and omega-3 fatty acids (n = 25). Reproductive outcomes were the most commonly reported (n = 285; 83%), followed by metabolic (n = 229; 67%), anthropometric (n = 197; 57%) and psychological (n = 8; 2%). Our results identified that nutraceutical and micronutrient supplementation require further investigation of psychological outcomes in women with PCOS. Moreover, adequately powered primary studies are warranted to investigate therapeutic doses needed for clinical benefits.